A new black fly species of Simulium (Nevermannia) (Simuliidae: Diptera) from the Southern Eastern Ghats, India - Anbalagan, Sankarappan; Rekha, Kalimuthu; Vijayan, Suruliyandi; Balachandran, Chellapandian; Dinakaran, Sundaram; Krishnan, Muthukalingan (Zootaxa, 2020)
A new black fly species, Simulium (Nevermannia) karavalliense sp. nov. is described from Southern Eastern Ghats of South India. This new species is placed in the Simulium ruficorne species-group of the subgenus Nevermannia. S. (N.) karavalliense sp. nov. is characterized by female with a long sensory vesicle, male upper eye with 14 vertical columns and 16 horizontal rows of large facets, pupal gill with 8 filaments and larval hypostoma with 6 hypostomal bristles lying parallel to lateral margin. Taxonomic keys are provided to distinguish this new species from related species in India.